Sensorless Control of BLDCs for All Speed Ranges with Minimal Components - Dusmez, S.; Khafigh, A.; Krishnamurthy, M.; Ugur, E.; Uzunoglu, M. (IEEE, 2011)
Sensorless control strategies for brushless DC motors (BLDC) offer cost-effective and fault tolerant operation through replacing expensive position sensors with low-cost circuit components or taking advantage of on-board components. These drives mainly focus on two individual issues; first one is finding the initial rotor position at standstill, and the second one is driving BLDC at high speeds. Most of the studies focus on these two cases separately, proposing different circuit for each of them which adds to cost of the system. Therefore, it is desired to have control over all speed ranges including zero speed with same circuit elements if possible. This manuscript proposes a sensorless control method that combines initial position estimation by analyzing the stator core saturation and detection of zero crossings of back emf voltage by utilizing low pass filters with the same circuit topology. Results verify that a cost-effective drive can be achieved with proposed add-on resistor configuration and control method.
Keywords: BLOC drive; initial position estimation; low pass filter; sensorless control; MOTORS; Energy & Fuels; Engineering